Desenvolvimento de um fotobiorreator de placas planas para cultivo de microalgas com alta densidade celular - Hinterholz, Camila Larissa (2018)
The objective of this study was to develop a laboratory-scale photobioreactor (PBR) capable of obtaining microalgae cultures with high cell density. For this, the cultivation of Poterioochromonas malhamensis was evaluated in a flat-plate PBR, built with a useful volume of 10 L. The microalga strain was isolated from an artificial lake from Toledo – PR. The whole study was based on the System Analysis Theory, in which the research was divided into four hierarchical levels. In the first level, the mass transfer (MT) parameters were evaluated by means of a fractionated factorial design (FFD) considering four factors: gas inlet flow (Qgas), CO2 in the inlet gas (φCO2), antifoam concentration (CAE) and salinity of the medium (φsal), whose adjustable values may represent the MT for the responses K_L a_(O_2 ),〖 K〗_L a_(CO_2 ),O_2^eq e CO_2^eq. Thus, the parameters K_L a_(O_2 ) (14.88 to 79.32 h-1) and K_L a_(CO_2 ) (0 to 125.40 h-1) were verified experimentally, as well as the equilibrium concentration variations: O_2^eq (37.33 to 99.66%) and CO_2^eq (0 to 98.33%) respectively, relative to the equilibrium values of the species dissolved in pure water. Still in the first level, the Euler-Euler model was used for the study of the fluid dynamics inside the PBR, with the software Comsol®, being evaluated three configurations: PBRA – without disperser; PBRB – with simple bubble disperser; and PBRC – with perforated disperser, whose bubble dispersion proposal ensured a higher frequency of the light-dark cycles, according to the simulations of water and bubbles flows performed in mono and multiphase systems, respectively. The influence of the bubble dispersion module on cell growth was verified experimentally with PBRA and PBRC runs, which showed a 175% increase in biomass production (15.7 g L-1) with use of PBRC. In the second hierarchical level, the tolerance of the strain to the adjustable conditions of the system was studied: Qgas, φCO2, in addition to temperature, lighting conditions, nutrient concentrations and organic carbon, using the pulse technique. Within the evaluated ranges, the results did not show inhibition of growth, but was accentuated in values above 30 °C. Also, at this level, assuming the production of 1 g L-1 biomass, M-8 and BG-11 media were optimized by linear mathematical programming, whose objective function subjected to constraints based elemental composition of the biomass. Therefore, the original and optimized media were evaluated regarding biomass production, as well as protein, carbohydrate, lipid and pigment chlorophyll-a, chlorophyll-b and carotenoids content of cells. ANOVA indicated the best medium for the production of biomass (M-8), whose optimized values were prepared in the nitrogen source evaluation cultures. In these, three inorganic sources – NH4NO3, NaNO3 and KNO3; and an organic – urea were compared, and it was verified by ANOVA that the most appropriate source for the production of biomass was urea. In the third hierarchical level, a growth model was proposed based on mass balances and the definitions of specific transformation velocity, conversion definition, CO2 and O2 dissociation reactions in water and Henry's Law. After applying the phenomenological modeling of unstructured and non-segregated models, a set of stoichiometric equations was built, which were used to evaluate kinetic models obtained from the literature, by which the influence of light, dissolved CO2 and O2, pH and temperature on cell growth. Using the results obtained at previous levels, the fourth-level study indicated that the simplified model proposed to describe the experimental data of Poterioochromonas malhamensis culture in closed PBR (cell growth, CO2 consumption in the gas phase, and variation in the pH of the medium) was adequate, whose simulations were also satisfactory for the consumption of the inorganic dissolved carbon species, as well as for the mass transfer between the phases. In this step, 32 kinetic and stoichiometric parameters were estimated in the fit of the proposed model to the experimental data, through an algorithm based on the Genetic Algorithms implemented in the software Maple®. Therefore, this study presented the use of the perforated bubble disperser module coupled to the proposed PBR, which allowed the achievement of what is characterized by ultra-high density culture, since ≈ 15 g L-1 of biomass were produced by the culture of P. malhamensis. It was also highlighted the possibility of optimizing important conditions for biomass cultivation, as well as for the design of PBRs, through the collection of experimental data, associated to appropriate statistical methodologies of evaluation and to kinetic and fluid dynamics modeling, according to the General Theory of Systems applied.